2013
DOI: 10.1080/1369183x.2013.723253
|View full text |Cite
|
Sign up to set email alerts
|

Regimes of Mobility Across the Globe

Abstract: Mobility studies emerged from a postmodern moment in which global 'flows' of capital, people and objects were increasingly noted and celebrated. Within this new scholarship, categories of migrancy are all seen through the same analytical lens. This article and Regimes of Mobility: Imaginaries and Relationalities of Power, the special issue of JEMS it introduces, build on, as well as critique, past and present studies of mobility. In so doing, this issue challenges conceptual orientations built on binaries of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
411
0
56

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 870 publications
(469 citation statements)
references
References 59 publications
(39 reference statements)
2
411
0
56
Order By: Relevance
“…Es decir, desde esta perspectiva es también posible visualizar desigualdades y procesos de precarización que se generan bajo los regímenes de la movilidad global contemporánea (Sheller, 2014;Glick-Schiller y Salazar, 2013). Al mismo tiempo, hace posible reconocer los intersticios por los que circulan personas, afectos, imágenes, códigos, pautas, discursos, objetos, bienes materiales y simbólicos, que a su vez configuran diferentes prác-ticas y experiencias tanto de movilidad como de establecimiento, lo mismo que culturas y geografías de movilidad/inmovilidad históricamente situadas (cf.…”
Section: El Problema De Investigación Y La Construcción Del Objeto Deunclassified
See 1 more Smart Citation
“…Es decir, desde esta perspectiva es también posible visualizar desigualdades y procesos de precarización que se generan bajo los regímenes de la movilidad global contemporánea (Sheller, 2014;Glick-Schiller y Salazar, 2013). Al mismo tiempo, hace posible reconocer los intersticios por los que circulan personas, afectos, imágenes, códigos, pautas, discursos, objetos, bienes materiales y simbólicos, que a su vez configuran diferentes prác-ticas y experiencias tanto de movilidad como de establecimiento, lo mismo que culturas y geografías de movilidad/inmovilidad históricamente situadas (cf.…”
Section: El Problema De Investigación Y La Construcción Del Objeto Deunclassified
“…Se informa de la perspectiva de las migraciones globales (Glick-Schiller, 2011;2012;Glick-Schiller y Salazar, 2013); retoma algunos principios metodológicos derivados de los estudios transnacionales, específicamente en la línea de lo que Khagram y Levitt (2008) definieron como transnacionalismo metodológico. Asimismo, recupera presupuestos de la perspectiva de las movilidades y las (in)movilidades geográficas y/o espaciales (Urry, 2007;Sheller y Urry, 2004;Sheller, 2011;Cresswell, 2006).…”
Section: Introductionunclassified
“…Mobility in social studies tends to be considered from the paradigm of new forms of mobility, establishing a connection between mobility and immobility in an attempt to identify the conditions under which this mobility occurs. It acts as a marker of social difference, and is possibly the most important social stratification factor currently in existence (Salazar and Smart, 2011;Glick Schiller and Salazar, 2013). Bergeon et al (2013) have shown that mobility and immobility 1 As this author points out, Mexican migration is characterised by an ongoing tension between the structure established outside Mexico and return, two alternatives which although always a possibility, "are conditioned by structural factors, yet always defined by projects, needs and desires, and above all by the migrants' economic, social and cultural resources" (1998) (author' translation).…”
Section: Introductionmentioning
confidence: 99%
“…These justifications are active within the household, shaping the attitudes adopted by various members towards the migration of women (separation from the home, abandonment of their children and the obligation to return) or men (justification of their role as breadwinners and 'punishment' in the event of failure to comply with this obligation). This discourse will allow us to identify the principal organisers of men and women's mobility-immobility axis in an interrelated rather than a fixed or static manner within the framework of global mobility regimes (Glick Schiller and Salazar, 2013 interviews were conducted with women, men and young people from households in which at least one member had returned or was in the process of doing so: a returned father/mother, son/daughter, brother/sister. Several members of each of the families were interviewed separately, including men and women from different generations in order to guarantee that the fieldwork included a gendered and intergenerational perspective.…”
Section: Introductionmentioning
confidence: 99%
“…As this book demonstrates, situating return mobility as a starting point for social inquiry, rather than a middle or end point, postscript or afterthought, gives rise to important questions regarding the broader context and experience of human mobility, community and identity. This, we argue, represents an important contribution to emerging perspectives that seek to move beyond binary optics of domestic or translocal versus international migration, local versus foreign identity, and indeed of stasis versus mobility itself (Glick Schiller and Salazar 2013; and for an excellent overview of Pacific scholarship, see Keck and Scheider 2015). More importantly still, the chapters collected here demonstrate the extent to which in the current 'age of migration' (Castles and Miller 2009) the prospect and practice of returning home, or of navigating returns between multiple homes, is a central rather than peripheral component of contemporary Pacific Islander mobilities and identities.…”
mentioning
confidence: 99%